2018
DOI: 10.34289/277898
|View full text |Cite
|
Sign up to set email alerts
|

Profil Berpikir Kritis Mahasiswa Program Studi Pendidikan Biologi Se-kota Pekanbaru

Abstract: Berfikir Kritis merupakan suatu proses di mana seseorang mencoba untuk menjawab pertanyaan-pertanyaan yang tidak mudah dijawab secara rasional sementara informasi yang relevan pun tidak tersedia. Berpikir kritis ini termasuk dalam kemampuan berpikir tingkat tinggi yang melibatkan proses yang kompleks.. Tujuan dari penelitian ini adalah untuk mengetahui profil berfikir kritis mahasiswa Program Studi Pendidikan Biologi yang ada di Kota Pekanbaru. Populasi pada penelitian ini adalah semua mahasiswa pendidikan bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 2 publications
2
6
0
4
Order By: Relevance
“…Based on table 3, we can see that the average of all components of the critical thinking profile of students of the undergraduate biology education program of Universitas Negeri Yogyakarta is in the fair category with a score of 71.74. This is in line with the current research performed by Idris which states that profile of undergraduate students' critical thinking in biology education study program at Pekanbaru, Indonesia is in the fair category [10]. From the initial critical thinking test conducted by Khasanah and Octaviani, it was also found that the critical thinking skills of students in the calculus course at Wisnuwardhana University Malang were in a fair category [23].…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Based on table 3, we can see that the average of all components of the critical thinking profile of students of the undergraduate biology education program of Universitas Negeri Yogyakarta is in the fair category with a score of 71.74. This is in line with the current research performed by Idris which states that profile of undergraduate students' critical thinking in biology education study program at Pekanbaru, Indonesia is in the fair category [10]. From the initial critical thinking test conducted by Khasanah and Octaviani, it was also found that the critical thinking skills of students in the calculus course at Wisnuwardhana University Malang were in a fair category [23].…”
Section: Resultssupporting
confidence: 88%
“…Through a good quality education, it is hoped that it can produce high quality human resources who are able to face various problems in this century [9]. The characteristics of quality graduates are one of them who has the skills to think critically [10] and think creatively [10] [11]. Critical thinking and creative thinking in students can be developed during the lecture process in higher education [12] [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hal ini juga tercantum dalam Permendikbud No 49 tahun 2014 tentang Standar Nasional Pendidikan Tinggi Pasal 6 bahwa lulusan program sarjana harus memiliki keterampilan umum diantaranya dapat bersikap dan berpikir secara logis, kritis, sistematis, serta memiliki inovasi dalam lingkup pengembangan ilmu pengetahuan dan teknologi dengan memperhatikan dan menerapkannya pada nilai humaniora yang disesuaikan dengan bidang keahlian. Namun, berdasarkan survei yang dilaksanakan oleh Idris (2018) dan Anugraheni (2020), mengungkap bahwa keterampilan berpikir kritis yang dimiliki mahasiswa masih tergolong rendah.…”
Section: Pendahuluanunclassified
“…Keterampilan berpikir kritis mahasiwa dapat ditingkatkan saat proses perkuliahan ketika mahasiswa menerima instruksi yang secara khusus dirancang dengan tujuan meningkatkan keterampilan berpikir kritis (Idris, 2018). Dengan menggunakan metode diskusi yang terarah, keterampilan berpikir kritis mahasiswa juga bisa dilatih dan dikembangkan (Kustyorini & Mashuri, 2019).…”
Section: Peningkatan Keterampilan Berpikir Kritis Dengan Model Inkuiri Terbimbingunclassified